Disease Course and Treatment Response of Eosinophilic Gastrointestinal Diseases in Children With Liver Transplantation: Long-Term Follow-Up. (13th January 2021) - Ozdogan, Elif; Doganay, Latife; Can, Demet; Arikan, Cigdem
Abstract : INTRODUCTION: To describe the clinical and laboratory profile, natural course, treatment outcome, and risk factors of posttransplant esophageal and nonesophageal eosinophilic gastrointestinal disorders (EGIDs). METHODS: All children (aged <18 years) who underwent liver transplantation, between 2011 and 2019, in a single transplant center with a follow-up period of 1 year or more posttransplant and with a history of posttransplant endoscopic evaluation were included in this study. RESULTS: During the study period, 89 children met the inclusion criteria. Patients were followed for a median of 8.0 years. A total of 39 (44%) patients were diagnosed with EGID after transplantation. Of these, 29 (33%) had eosinophilic esophagitis (EoE), and 10 (11%) had eosinophilic gastritis, gastroenteritis or enterocolitis. In comparison with the non-EGID group, patients with EGID were younger at transplant ( P ≤ 0.0001), transplanted more frequently due to biliary atresia ( P ≤ 0.0001), and had higher rates of pretransplant allergy ( P = 0.019). In the posttransplant period, they had higher rates of mammalian Target of Rapamycin inhibitor use ( P = 0.006), Epstein-Barr virus viremia ( P = 0.03), post-transplant lymphoproliferative disease ( P = 0.005), and allergen sensitization ( P ≤ 0.0001). In regression analysis, young age at transplant, age at diagnosis, pretransplant atopic dermatitis, and post-transplant lymphoproliferative disease were associated with an increased risk of EGID or EoE. Laboratory abnormalities such as anemia ( P = 0.007), thrombocytosis ( P = 0.012), and hypoalbuminemia ( P = 0.031) were more commonly observed in the eosinophilic gastritis, gastroenteritis or enterocolitis group than in the EoE group. Following treatment, most patients had symptomatic resolution at 3 months and histologic resolution at 6 months postdiagnosis. Among the patients who had 5 years of follow-up, none recurred. DISCUSSION: EGID is a common posttransplant diagnosis, which seems to affect patients who are transplanted earlier and who have pretransplant atopy. Posttransplant EGID is responsive to treatment, but as histologic remission occurs after symptomatic resolution, the decision to perform control endoscopy should be delayed.